2021
DOI: 10.1371/journal.pone.0259534
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarkers for predicting papillary thyroid carcinoma patients at high risk using nine genes of apoptotic pathway

Abstract: Aberrant expressions of apoptotic genes have been associated with papillary thyroid carcinoma (PTC) in the past, however, their prognostic role and utility as biomarkers remains poorly understood. In this study, we analysed 505 PTC patients by employing Cox-PH regression techniques, prognostic index models and machine learning methods to elucidate the relationship between overall survival (OS) of PTC patients and 165 apoptosis related genes. It was observed that nine genes (ANXA1, TGFBR3, CLU, PSEN1, TNFRSF12A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Zeng Ye et al discovered that FBW7 enhanced the lethal effect of gemcitabine in pancreatic cancer by inducing ferroptosis and apoptosis [ 20 ]. In previous studies, BID, FBXW7, and GPX4 had already been found to be significant in thyroid cancer [ 21 , 22 , 23 ], whereas the role of AKR1C3 and MAP3K5 in the development and progression of thyroid cancer has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng Ye et al discovered that FBW7 enhanced the lethal effect of gemcitabine in pancreatic cancer by inducing ferroptosis and apoptosis [ 20 ]. In previous studies, BID, FBXW7, and GPX4 had already been found to be significant in thyroid cancer [ 21 , 22 , 23 ], whereas the role of AKR1C3 and MAP3K5 in the development and progression of thyroid cancer has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The embedded technique merges both filter-wrapper methods, integrating the training procedure to the feature selection procedure to determine the optimal feature subset. One popular technique of feature selection in embedded methods is the least absolute shrinkage and selector operation (LASSO) method, which has been widely used to identify predictive and prognostic biomarkers as seen in [18,23,26,32,37,38]. Additionally, LASSSO was used to identify important features in most of the subgroup analyses.…”
Section: Rq1: What Machine Learning Models Are Currently Being Used T...mentioning
confidence: 99%
“…3,29 The role of BRAF V600E mutation in benign-malignant discrimination, aggressiveness, prognosis and targeted therapy has been confirmed by various studies. 8,[30][31][32] Li et al 33 suggested that BRAF V600E mutation test was highly recommended in mutation endemic areas. However, the BRAF V600E mutation status needs to be obtained by puncture biopsy or postoperative pathology, and genetic sequencing is time-consuming and expensive.…”
Section: Predictive Performance Of Three Modelsmentioning
confidence: 99%